Monetary policy in an oil-dependent economy in the presence of multiple shocks - Andrej Drygalla (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2017)
Russian monetary policy has been challenged by large and continuous private capital outflows and a sharp drop in oil prices during 2014, with both ongoings having put a significant depreciation pressure on the ruble and having led the central bank to eventually give up its exchange rate management strategy. Against this background, this paper estimates a small open economy model for Russia, featuring an oil price sector and extended by a specification of the foreign exchange market to correctly account for systematic central bank interventions. We find that shocks to the oil price and private capital flows substantially affect domestic variables such as inflation, output and the exchange rate. Simulations of the model for the estimated actual strategy and five alternative regimes suggest that the vulnerability of the Russian economy to external shocks can substantially be lowered by adopting some form of an inflation targeting strategy. Foreign exchange intervention-based policy strategies to target the nominal exchange rate or the ruble price of oil, on the other hand, prove inferior to the policy in place.
urn:nbn:de:gbv:3:2-73633
Keywords: E52; F31; F41; G15; 330; monetary policy; exchange rate interventions; oil price; capital flows